1992
DOI: 10.1080/09540109209354774
|View full text |Cite
|
Sign up to set email alerts
|

Influence of apo‐ and iron‐saturated lactoferrin and transferrin, immunoglobulin G and serum albumin on proliferation of bovine peripheral blood mononuclear cells

Abstract: 1992) Influence of apo-and iron-saturated lactoferrin and transferrin, immunoglobulin G and serum albumin on proliferation of bovine peripheral blood mononuclear cells, Food and Agricultural Immunology, 4:4, 253-257, Whey proteins from non-lactating bovine mammary secretions reduced peripheral blood mononuclear cell (PBMC) response to mitogens. Specific proteins responsible for hyporesponsiveness are unknown. This study evaluated the influence of apo-and ironsaturated lactoferrin (APOLF and FELF) and transferr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 9 publications
1
10
1
Order By: Relevance
“…Downloaded by [University of Saskatchewan Library] at 10:34 19 November 2014 Slater and Fletcher (1987) reported that human holo-lactotransferrin inhibited the uptake of tritiated uridine by allogenic mixed lymphocyte cultures whereas apo-lactotransferrin did not. A significant difference between the influence of apo-serotransferrin and holo-serotransferrin on Con A-induced bovine blood lymphocyte proliferation was observed (Rejman et al, 1992). In the present work, however, apo-bLf, cOf and qOf were as effective as holo-transferrins to cause cytotoxicity for mouse lymphocytes and to inhibit the proliferation of mouse lymphocytes (Figure 2).…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…Downloaded by [University of Saskatchewan Library] at 10:34 19 November 2014 Slater and Fletcher (1987) reported that human holo-lactotransferrin inhibited the uptake of tritiated uridine by allogenic mixed lymphocyte cultures whereas apo-lactotransferrin did not. A significant difference between the influence of apo-serotransferrin and holo-serotransferrin on Con A-induced bovine blood lymphocyte proliferation was observed (Rejman et al, 1992). In the present work, however, apo-bLf, cOf and qOf were as effective as holo-transferrins to cause cytotoxicity for mouse lymphocytes and to inhibit the proliferation of mouse lymphocytes (Figure 2).…”
Section: Discussioncontrasting
confidence: 43%
“…Ashorn et al (1986) and Richie et al (1987) showed that human lactotransferrin suppressed the Con A-and PHA-induced proliferation respectively of human lymphocytes. Rejman et al (1992) observed that bovine serotransferrin and lactotransferrin suppressed the Con A-induced proliferation of bovine peripheral blood lymphocytes. More recently, Otani et al (1995b) reported that quail egg-white ovotransferrin inhibited Con Aand PHA-induced proliferation of mouse lymphocytes.…”
Section: Introductionmentioning
confidence: 96%
“…It is known that beta‐and kappa‐casein (in particular the carbohydrate‐rich glycomacropeptide component of the latter) have a variety of suppressive and stimulatory effects on mononuclear cell function 2 , 3 , 5 , 6 , 7 , 8 , 9 . In addition, some of the proteins isolated and purified from whey have been shown to be potent modulators of cellular immune function; these include lactoperoxidase, lactoferrin, and milk growth factor 4 , 8 , 10 , 11 . In general, the immunomodulatory function of these individual components becomes more evident (and the dose response more potent) as they are progressively purified from whole casein or whey 8 .…”
Section: Introductionmentioning
confidence: 99%
“…The proliferation of PBMCs in response to mitogens decreased when they were cultured in the presence of mammary secretions (Torre & Oliver, 1989). Recent evidence identified LF, a major component of bovine mammary secretions during the non-lactating period (Welty et ah, 1976), as having the greatest negative influence on response of PBMC to Con A (Rejman et al, 1992). Richie et a/.…”
Section: Discussionmentioning
confidence: 96%
“…Intact mammary secretions obtained during the non-lactating period elicited a greater reduction of PBMC proliferation in response to mitogens than secretions from lactating cows (Torre & Oliver, 1989). In similar experiments using purified mammary secretion whey proteins, lactoferrin (LF) was associated with the greatest reduction of PBMC proliferation in response to concanavalin A (Con A; Rejman et al, 1992). Thus, the environment in which mononuclear cells must function may significantly influence their response.…”
Section: Introductionmentioning
confidence: 90%